2009
DOI: 10.1111/j.1744-7348.2009.00319.x
|View full text |Cite
|
Sign up to set email alerts
|

Viruses in soils: morphological diversity and abundance in the rhizosphere

Abstract: Soil viruses are potentially of great importance as they may influence the ecology and evolution of soil biological communities through both an ability to transfer genes from host to host and as a potential cause of microbial mortality. Despite this importance, the area of soil virology is understudied. Here, we report the isolation and preliminary characterisation of viruses from soils in the Dundee area of Scotland. Different virus morphotypes including tailed, polyhedral (spherical), rod shaped, filamentous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
60
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(63 citation statements)
references
References 36 publications
3
60
0
Order By: Relevance
“…Our electron microscopy observations showed that the abundance of virus-like particles in four soil types in this study is of the same order as that found previously in brown earth soil from the Dundee area (10). However, sometimes differences in virus abundances in different soils can be seen, which appear to correlate with soil moisture and organic matter content (4), and this may be due to specific environmental conditions pertinent to those soils.…”
Section: Discussionsupporting
confidence: 54%
See 3 more Smart Citations
“…Our electron microscopy observations showed that the abundance of virus-like particles in four soil types in this study is of the same order as that found previously in brown earth soil from the Dundee area (10). However, sometimes differences in virus abundances in different soils can be seen, which appear to correlate with soil moisture and organic matter content (4), and this may be due to specific environmental conditions pertinent to those soils.…”
Section: Discussionsupporting
confidence: 54%
“…A method for the extraction of viruses from 1-g samples of soils was adapted from the method described by Swanson et al (10). One-gram soil samples were divided equally between two 2-ml Eppendorf tubes, and 1 ml of 0.067 M phosphate buffer, pH 7.5, and 250 l of 1-mm-diameter sterile glass beads were added to each tube, which was shaken in a Qiagen Retsch tissue lyser for 5 min at 30 revolutions s Ϫ1 .…”
Section: Virus Purificationmentioning
confidence: 99%
See 2 more Smart Citations
“…However Coleman ( 2011 ) points out that little attention has been given to viruses in soil, despite the understanding that a small but signifi cant amount of C is cycled through viral components in pelagic ecosystems. Small spherical viruses form the major portion of the morphological classes of virus in soil under wheat cultivation (Swanson et al 2011 ) and it is interesting that they show no difference in viral abundance between rhizosheath, rhizosphere and bulk soil despite a signifi cant reduction in bacterial numbers in bulk soil compared to the rhizosphere. This suggests that many viruses in soil are not directly associated with bacterial hosts.…”
Section: Virusesmentioning
confidence: 99%